Edukasi tentang Etika dalam Teknologi Komunikasi dan Kemampuan Berpikir Kritis Pada Siswa SMAN 13 Maros - Sartika; Sani, Andi (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
The era of digitalization and the rapid development of technology, especially the internet, has led to the openness of communication without knowing the boundaries of space and time.communication without recognizing the boundaries of time and space. Digital interactions that occur between genders, and between other social groups, can tell all information without limits. other social groups, can share all information without limits. All digital interactions on social media can All digital interactions on social media can raise ethical issues, meaning that in this digital space, we will interact and communicate with various cultural differences, so thatwith these cultural differences, so it is very likely that the global meeting will create new standards of ethics. create new standards of ethics. This Community Service aims to provide education to teenagers about ethics in communication technology and improve critical thinking skills using the lecture method. lecture method. The activity was attended by 30 students of SMAN 13 Maros. Community service activities in the form of education model education model to students of SMAN 13 Maros was well implemented and resulted in an increase in knowledge of ethics in technology and critical thinking skills. about ethics in technology and critical thinking skills by 55.4%. It is expected that educational activities andtraining activities with the theme of improving students' skills and thinking abilities can be carried out regularly and get support from the school